Mechanism of regulation of the 422(aP2) gene by cAMP during preadipocyte differentiation. - Yang, V W (1989)
During differentiation of 3T3-L1 preadipocytes into adipocytes, expression of the gene encoding adipocyte 422(aP2) protein is activated. We have shown that the first 248 base pairs of the 422(aP2) gene promoter (which lacks a consensus cAMP response element) are sufficient to confer inducibility of a reporter gene by cAMP in preadipocytes. We now demonstrate by deletion analysis that this DNA segment contains overlapping negative and positive regulatory elements. The positive regulatory element contains a consensus activator protein 1 (AP-1) binding sequence. The effect of the negative regulatory element is observed in preadipocytes but not in fully differentiated adipocytes, suggesting that it is an important component of the regulatory mechanism governing expression of the 422(aP2) gene during differentiation. cAMP activates the 422(aP2) promoter in confluent preadipocytes but not in proliferating preadipocytes or fully differentiated adipocytes. The stimulatory effect of cAMP is abolished by deletions that enter the negative element, suggesting that cAMP increases expression by relieving the inhibitory effect of the negative regulatory element.